Disentangling inflammatory from fibrotic disease activity by fibroblast activation protein imaging - Schmidkonz, Christian; Rauber, Simon; Atzinger, Armin; Götz, Theresa Ida; Soare, A.; Cordes, Michael; Prante, Olaf; Ritt, Philipp; Bäuerle, Tobias; Köhner, Markus; Haberkorn, U.; Kuwert, Torsten; et al. (European Journal of Nuclear Medicine and Molecular Imaging, 2021)
Ziel/Aim To date, there is no valuable tool to assess fibrotic disease activity in humans in vivo in a non-invasive way. This study aims to uncouple inflammatory from fibrotic disease activity in fibroinflammatory diseases such as IgG4-related disease. Methodik/Methods In this cross-sectional clinical study, 27 patients with inflammatory, fibrotic and overlapping manifestations of IgG4-related disease underwent positron emission tomography (PET) scanning with tracers specific for fibroblast activation protein (FAP; 68Ga-FAP inhibitor (FAPI)-04), 18F-fluorodeoxyglucose (FDG), magnetic resonance imaging (MRI) and histopathological assessment. In a longitudinal approach, 18F-FDG and 68Ga-FAPI-04 PET/CT data were evaluated before and after immunosuppressive treatment and correlated to clinical and MRI data. Ergebnisse/Results Using combination of 68Ga-FAPI-04 and 18F-FDG-PET, we demonstrate that non-invasive functional tracking of IgG4-related disease evolution from inflammatory towards a fibrotic outcome becomes feasible. 18F-FDG-PET positive lesions showed dense lymphoplasmacytic infiltration of IgG4 + cells in histology, while 68Ga-FAPI-04 PET positive lesions showed abundant activated fibroblasts expressing FAP according to results from RNA-sequencing of activated fibroblasts. The responsiveness of fibrotic lesions to anti-inflammatory treatment was far less pronounced than that of inflammatory lesions. Schlussfolgerungen/Conclusions FAP-specific PET/CT permits the discrimination between inflammatory and fibrotic activity in IgG4-related disease. This finding may profoundly change the management of certain forms of immune-mediated disease, such as IgG4-related disease, as subtypes dominated by fibrosis may require different approaches to control disease progression, for example, specific antifibrotic agents rather than broad spectrum anti-inflammatory treatments such as glucocorticoids.
CRIS-Team WoS Importer:2022-01-07